الأفعال التي تنصب مفعولا به أشكالها وخصائصها التركيبية في كتاب رياض الصالحين - Nasirah binti Ismail (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The study focuses on the book Riyad al-Salihin written by Imam Yahya ibn Sharaf al-Nawawi (may Allah have mercy upon him) (631-676 A.H). The objective of the research is to examine the type of transitive verbs mentioned in the book. In order to identify the rules of the verb in the hadith collection, the researcher highlights some issues by examining the form structures of the hadith mentioned. This study divided the analysis into four sections: types of accusative object, di-transitive verbs in governing the accusative object, rearrangement and ellipsis rules of sentences, and the distinct in usage of the transitive verb in Riyad al-Salihin. The research adopts both inductive and analytical approaches. The significance of this research is that it offers more insights into a more comprehensive design of the linguistic curriculum design in Quranic and Hadith study.